EFEKTIVITAS PROSES REKRUTMEN DAN SELEKSI DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI ORGANISASI PENDIDIKAN - Salam, Ifriani Abdul; S., Siti Munawirah; Octaviana, Wahida; Sumiati, Sumiati (IQRA : JURNAL PENDIDIKAN ISLAM, 2024)
Human resources are one of the important components which is the basic capital in building and running a company. Human resources are needed to aim to help the company achieve the success that has been determined and to fill the vacancies in accordance with previous planning. With the existence of human resources who have good performance and are competent in their fields, the company will be able to operate optimally. Literature study techniques are used to collect data from various sources such as journals, articles, and other documents related to Recruitment and Selection. The collected data will be analyzed using a descriptive method. Descriptive methods are used to describe and explain the data obtained. Data analysis will be carried out by reading, understanding, and interpreting data that has been collected from various sources. The data that has been analyzed will be presented in the form of a structured and systematic narrative. The researcher intends to reveal whether the recruitment and selection process can run ineffectively and then it is found that if the human resources who register do not meet the expected numbers and the applicant has criteria that do not meet the predetermined classification, then it can be said that the recruitment and selection process is ineffective. Factors that underlie ineffectiveness in recruitment and selection.